Pemanfaatan Aplikasi Sentuh Tanahku Guna Perbaikan Kinerja Layanan di Kantor Pertanahan Kota Palangka Raya - Mariana Derlan Masia Harahap; Ferdinand Ferdinand; Luluk Tri Harinie (Edunomics Journal, 2023)
This study aims 1) To reveal how the impact of changes in the use of service systems from non-electronic data to electronic data for the Internal Land Office and the Community at the Land Office of the City of Palangka Raya, 2) To reveal how the service performance process is done electronically by using the Touch Tanahku Application at the Land Office of the City of Palangka Raya, and 3) To reveal how the obstacles encountered in improving service performance with the Touch Tanahku application at the Land Office of the City of Palangka Raya. This research is a qualitative research with data analysis using the Miles and Huberman technique, where activities in qualitative data analysis are carried out interactively with State Civil Servants, Notaries/PPAT, and service users at the Land Office of the City of Palangka Raya. The results of this study reveal that 1) The existence of an electronic service system and land service information through the Touch Tanahku Application has an impact on increasing public information disclosure, services that are faster, accurate and safer, as well as providing convenience for the public to obtain certainty of service information; 2) The existence of land services electronically can improve the performance of land services in accordance with service standards, namely timeliness, transparency, and increasing community satisfaction; and 3) Obstacles faced are the need to improve the quality of land data, the need for synchronization and harmonization in the Touch Tanahku Application, and the need for outreach to the public regarding the use of the Touch Tanahku Application.